2022
DOI: 10.29303/jppi.v2i2.1334
|View full text |Cite
|
Sign up to set email alerts
|

Diseminasi Pengolahan Sederhana Limbah Ikan Sebagai Dedak

Abstract: Limbah hasil pengolahan ikan asin di Desa Batu Belubang Kecamatan Pangkalan Baru Kabupaten Bangka Tengah, dapat dikeringkan menjadi dedak ikan sebagai bahan baku pakan ikan budidaya dan pakan ternak lainnya. Dedak bernilai ekonomi, dan dapat dijual dengan harga Rp 4.000/kg. Tujuan kegiatan Pengabdian kepada Masyarakat (PkM) adalah membantu nelayan tradisional mendapatkan usaha sampingan dari pengolahan limbah ikan menjadi dedak/tepung ikan bernilai ekonomi tinggi. Pelaksanaan PkM adalah partisipatif atau melib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Furthermore, as users, small fishermen are vulnerable due to experiencing the most pressure from the impact of the trade-off (Mardyani and Lindawati 2021). This study also revealed that the allocation of coastal and marine space on Bangka Island, which is dominated by mining activities, has caused various problems, especially for capture fisheries activities (Nurtjahya and Agustina 2015;Manik 2018;Pratama 2018;Bidayani and Hartoko 2019;Ramadona et al 2020;Bidayani and Reniati 2021;Bidayani and Priyambada 2022). In addition, the existence of a marine Mining Business Permit (IUP) adjacent to the location of the fishing area (DPI) causes conflicts with local fishermen (Ibrahim et al 2018;Sulista et al 2019).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, as users, small fishermen are vulnerable due to experiencing the most pressure from the impact of the trade-off (Mardyani and Lindawati 2021). This study also revealed that the allocation of coastal and marine space on Bangka Island, which is dominated by mining activities, has caused various problems, especially for capture fisheries activities (Nurtjahya and Agustina 2015;Manik 2018;Pratama 2018;Bidayani and Hartoko 2019;Ramadona et al 2020;Bidayani and Reniati 2021;Bidayani and Priyambada 2022). In addition, the existence of a marine Mining Business Permit (IUP) adjacent to the location of the fishing area (DPI) causes conflicts with local fishermen (Ibrahim et al 2018;Sulista et al 2019).…”
Section: Discussionmentioning
confidence: 94%
“…This concept is an economic development that relies on marine resources associated with sustainable resource management and focuses on three perspectives: economic, ecological, and social factors. The blue economy emphasizes innovation more to meet fishermen's needs through increasing added value at every stage, thus requiring innovation skills (Bidayani and Priyambada 2022). However, economic activities in the coastal area of Batu Belubang Village, Pangkalan Baru Sub-district, and Central Bangka District can cause conflict due to unconventional tin mining activities and limited capture fisheries in the village area (Bidayani 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Strategy determination is based on visi and mission Kasih Sayang Mangrove Ecotourism Area, IFE Matrix, EFE Matrix, IE Matriks, blue economy indicators, blue economy general strategy, dan blue economy strategy previous research [8][10] [11].…”
Section: Calculation Ife Matrix and Efe Matrix Valuesmentioning
confidence: 99%